Control strategies for active distribution networks based on soft open point - Jia, Chunhe; Chen, Xiangyu; Yan, Chao; Li, Zhengjun; Wang, Chunguang; Li, Haolin; Zhang, Song; Huang, Botao (Frontiers in Energy Research, 2023)
The application of SOP instead of traditional tie line switches in distribution networks can im-prove the controllability, flexibility, and renewable energy accommodation of the distribution grids. Compared with traditional tie line switches, SOP have high costs and large land occupation. When power transfer is not considered, the location and capacity of SOP can be optimized through planning algorithms to reduce the overall costs. However, the main function of tie line switches is power transfer. If SOP as alternative devices do not meet this requirement, their ex-tensive application will be restricted. Therefore, this paper designs the direct current volt-age-power smooth switching control strategy, phase angle pre-synchronization control strategy, and voltage support control strategy based on the parallel structure of SOP and tie line switches to ensure stable operation during the power transfer process, through this complete control strategy, smooth switching can be achieved to keep the DC voltage stable during the switching process, effectively suppress the impulse current and maximize the utilization of SOP capacity Simulations on the SIMULINK plat-form verify the feasibility of the control strategies.